Majelis Sholawat Sebagai Upaya Pemberdayaan Ekonomi Masyarakat di Wilayah Pedesaan - Khoiruddin, Muh.; Purnomo, Hari; Hoirul, Imam; Umami, Arisa Fitri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2024)
Community economic empowerment is an important strategy in improving welfare and economic independence at the village level. This study focuses on the implementation of economic empowerment in Parijatahwetan Village through various initiatives involving skills training, the formation of business groups, and increasing access to capital. The Majelis Solawat, as one of the main forums in the village, plays an important role in this initiative by integrating religious activities with economic development. The research method used in this study is qualitative research. Data collection techniques used are observation, interviews and documentation. Data analysis using interactive analysis with stages of data collection, data presentation, data reduction and drawing conclusions. The results of the study show that the Majelis Sholawat in Parijatahwetan Village plays an important role in strengthening religious identity and strengthening community faith through reading and respect for the Prophet Muhammad SAW. In addition to the spiritual aspect, the Majelis Sholawat also has great potential to support local economic empowerment. Attracting community participation and visitors from outside the region, this event creates economic opportunities through increasing local trade, developing transportation services, and accommodation